Комплект нормативных документов по разработке и изданию учебных материалов - Шамина О. Б. Ольга Борисовна; Малышенко А. М. Александр Максимович; Гормаков А. Н. Анатолий Николаевич; Горисев С. А. Сергей Алексеевич; Беломестнова Э. Н. Эмилия Николаевна; Горбунова Н. Я. Нина Яковлевна (Томск, Изд-во ТПУ, 2014)
Заглавие с титульного экрана